Mejora de un proceso productivo de cultivo hidropónico empleado para el consumo animal. - Portero Aponte, Flavio Joel (2020)
Agricultural production of foliage for animal consumption in several sectors of Ecuador is reduced due to poor soil conditions, either due to its aridity or lack of irrigation water. For this reason, the use of hydroponics is one of the alternatives to afford the problem. The purpose of this research work has been to improve the hydroponic foliage production system of oats, so that it has an automated drip and sprinkler irrigation system in a closed cycle; in this way it has been proposed to reduce excessive water losses and feed three rabbits, used as test animals, with the hydroponic foliage of oats obtained. Since a causal investigation and to carry out the objectives of the project, designs of structures and irrigation systems were developed, in addition, observation techniques and instruments such as control and registration sheets have been applied, also, engineering tools were used for the obtaining and representing data and results such as flowcharts, Histograms, Pareto diagrams, also a PLC programming software and structural design. Once the research resources were applied, the critical points of the old foliage production system were identified: an inefficient irrigation system, inadequate water quantities and times, which affected the production and quality of hydroponic foliage. Finally, with the implementation of the design and automation of the irrigation system, the production process was improved by 29.85%, in addition the water consumption was reduced by 51%, better quality oat foliage was obtained and the test animals grew best with hydroponic foliage food, compared to a referential test subject.